Pengaruh Model Pembelajaran Team Game Tournament (TGT) Menggunakan Media Question Card Terhadap Hasil Belajar Fiqih - Zulfa Nur Hasanah; Syarifah Gustiwati; Dewi Anggaryni (Jurnal Cakrawala Akademika, 2024)
This research is motivated by student learning outcomes that are not optimal, the lack of use of innovative and interesting learning models in Fiqh subjects. The purpose of this study was to determine the effect of the Team Game Tournament (TGT) cooperative learning model using the Question Card media on the results of learning Fiqh. The research method used was a quasi-experimental quantitative method (quasi-experimental) in this study using an experimental class and a control class. The experimental class uses the Team Game Tournament (TGT) cooperative learning model and the control class uses the conventional learning model. In this study the samples were taken using the side purposing technique and then redominated which resulted in 30 students in the experimental class and 30 students in the control class, so that the total number of samples was 60 students. The results of this study indicate that there is an influence of the Team Game Tournament (TGT) cooperative learning model on student learning outcomes in the Fiqh subject with an increase in learning outcomes which shows an average score of 50% in the pretest and 87% in the posttest in the experimental class